Bacteriological profiles, antimicrobial resistance patterns, and predictors of culture-confirmed neonatal Sepsis at Asella Teaching Hospital, Southeast Ethiopia - Mesfin Wubishet Gurmu; Samuel Manahle; Tesfa G/meskel; Solomon Gelaye Yinges; Gebi Agero; Liyat Kebede (PLoS ONE, 2026)
Background Neonatal sepsis remains a major cause of morbidity and mortality in low- and middle-income countries. Empirical antibiotic therapy is commonly initiated before culture results are available, in accordance with World Health Organization (WHO) recommendations; however, its effectiveness depends on local pathogen distribution and antimicrobial resistance patterns, which vary across healthcare settings. This study aimed to determine the bacteriological profile, antimicrobial susceptibility patterns, and predictors of culture-confirmed neonatal sepsis at Asella Teaching Hospital in Southeast Ethiopia. Methods A retrospective cross-sectional study was conducted among 392 neonates with clinically suspected sepsis who were admitted to the NICU between January 2021 and December 2023. Participants were selected using systematic random sampling from medical registry records. Blood cultures and bacterial identification were performed using standard microbiological procedures. Antimicrobial susceptibility testing was conducted using the Kirby–Bauer disk diffusion method in accordance with CLSI 2021 guidelines. Multivariable logistic regression analysis was used to identify independent predictors of culture-confirmed sepsis, with statistical significance set at p < 0.05. Results Culture-confirmed sepsis was identified in 246 neonates (62.8%; 95% CI: 57.9–67.1), with early-onset sepsis accounting for 71.9% of cases. Gram-positive (50.8%) and Gram-negative (49.2%) organisms were nearly equally distributed. Among Gram-positive isolates, coagulase-negative staphylococci (35%) and Staphylococcus aureus (8.1%) were predominant, whereas Klebsiella pneumoniae (22.4%) and Acinetobacter spp. (8.5%) were the leading Gram-negative pathogens. Gram-positive isolates showed the highest susceptibility to vancomycin (91.9%), followed by trimethoprim–sulfamethoxazole (76.3%) and amikacin (72.9%), while high resistance was observed to ampicillin (91.9%) and ciprofloxacin (80.5%). Gram-negative isolates were most susceptible to amikacin (85.8%) and carbapenems (75.8%), but demonstrated substantial resistance to ampicillin (92.5%) and third-generation cephalosporins (65.8–93.3%). Multivariable logistic regression analysis identified several independent predictors of culture-confirmed neonatal sepsis, including preterm birth (AOR = 2.20; 95% CI: 1.07–4.98), tachypnea at admission (AOR = 4.79; 95% CI: 2.73–8.41), hypothermia (AOR = 2.35; 95% CI: 1.12–4.92), prolonged hospitalization (AOR = 2.51; 95% CI: 1.52–4.16), maternal chorioamnionitis (AOR = 4.49; 95% CI: 2.35–8.80), and a low fifth-minute Apgar score (AOR = 3.95; 95% CI: 1.87–8.34). Conclusion Culture-confirmed neonatal sepsis was highly prevalent, with a substantial burden of multidrug-resistant pathogens. Most bacterial isolates exhibited high resistance to commonly used first-line antibiotics, whereas amikacin and carbapenems remained relatively effective. The high prevalence of multidrug-resistant Gram-negative bacteremia is particularly concerning and underscores the need for routine antimicrobial resistance surveillance, locally guided empirical antibiotic therapy, strengthened infection prevention and control measures, and robust antimicrobial stewardship programs to reduce the emergence of antimicrobial resistance and improve neonatal outcomes in this setting.